Aplikasi Ekstrak Rebung (Gigantochloa apus) dan Telur Keong Mas (Pomacea canaliculata) Sebagai Biofertilizer Terhadap Pematahan Dormansi Benih Andaliman (Zanthoxylum acanthopodium) - Simarmata, Putriani; Fitriani, Fitriani; Arico, Zulfan (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
Andaliman is an endemic plant in Indonesia and a characteristic spice of the Batak ethnic group. Its seeds have a low germination rate, around 14%, due to a hard seed coat structure that hinders water imbibition and gas exchange. To improve seed viability, biofertilizer from bamboo shoot extract and golden apple snail egg extract was used. This study aimed to determine the effect of this biofertilizer on breaking seed dormancy in Andaliman and its effective concentration. The experiment used a completely randomized design (CRD) with 9 treatments and 5 replications. Data were analyzed using ANOVA at a 5% significance level, followed by LSD tests. Results showed no significant effect of the biofertilizer on breaking dormancy but influenced the percentage of intact, cracked, filled, and empty seeds. A 50% golden apple snail egg extract concentration (PS2) increased intact, cracked, filled, and empty seeds to 84, 16, 84, and 16%, respectively, after 72 days of storage (DAS).